2019
DOI: 10.1186/s12944-019-0990-y
|View full text |Cite
|
Sign up to set email alerts
|

Double bonds of unsaturated fatty acids differentially regulate mitochondrial cardiolipin remodeling

Abstract: Background Supplemented fatty acids can incorporate into cardiolipin (CL) and affect its remodeling. The change in CL species may alter the mitochondrial membrane composition, potentially disturbing the mitochondrial structure and function during inflammation. Method To investigate the effect of the unsaturation of fatty acids on CL, we supplemented macrophage-like RAW264.7 cells with 18-carbon unsaturated fatty acids including oleic acid (OA, 18:1), linoleic acid (LA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…GO and KEGG analyses confirmed the involvement of FADS1 in fatty acid metabolism, including long-chain fatty acid metabolic processing, which is essential for functional activity in mitochondria [18]. In addition, PUFA could regulate mitochondrial membrane structure and function [19]. Previous study indicated that there are significant differences in the mitochondrial morphology of vitiligo skin compared with that in health skin [20].…”
Section: Discussionmentioning
confidence: 76%
“…GO and KEGG analyses confirmed the involvement of FADS1 in fatty acid metabolism, including long-chain fatty acid metabolic processing, which is essential for functional activity in mitochondria [18]. In addition, PUFA could regulate mitochondrial membrane structure and function [19]. Previous study indicated that there are significant differences in the mitochondrial morphology of vitiligo skin compared with that in health skin [20].…”
Section: Discussionmentioning
confidence: 76%
“…Our present data are limited to model experiments that must have confirmation for their application to biological systems. Two scenarios relevant for our data can be depicted: (i) the presence of H 2 S, at remarkable concentrations after its enzymatic production in mitochondria [ 55 , 56 ], and the isomerizing ability of its small diffusible radicals, such as HS • or the deprotonated form S •− [ 57 ], suggesting to monitor mitochondria with in vitro and in vivo experiments; (ii) the CL oxidation and the effects of several protective agents, monitored by the increase in CL contents [ 24 ], indicating the importance of a follow-up of CL isomerization under various stress conditions, in order to individuate antioxidants able to also preserve the natural cis double bond geometry [ 28 ]. The need for a multidisciplinary approach in the study of this interesting biomolecule clearly emerges.…”
Section: Discussionmentioning
confidence: 99%
“…The analytical aspect concerning the identification of trans CL isomers is a crucial issue to address, with the specific goal to have protocols that can examine biological specimens. At present, CL analysis includes: (i) the isolation of CL via preparative thin layer chromatography (TLC) and transesterification to obtain the corresponding fatty acid methyl esters (FAME) under acidic conditions (HCl, H 2 SO 4 or BF 3 in methanol) to proceed with the gas chromatographic (GC) identification of the fatty acid residues [ 21 , 22 , 23 , 24 ]; (ii) HPLC with tandem MS/MS analysis to identify cardiolipins among other lipid classes [ 25 , 26 , 27 , 28 , 29 ]. Based on our experience in fatty acid-based lipidomics [ 2 , 19 ], the transesterification conditions must ensure a quantitative performance and the analytical conditions need to separate and identify cis and trans isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiolipin can interact with the respiratory chain complexes and contribute to generate the electrochemical gradient. Additionally, since it can interact with death-inducing proteins, it is involved in the apoptotic process and oxidation of cardiolipin compromises apoptosis, promoting neuronal dysfunctions and the progression of neurodegeneration (e.g., Alzheimer's and Parkinson's disease) [80,81]. Coherently with this picture, plenty of studies highlight the involvement of mitochondrial dysfunctions in neurodegeneration [3,[82][83][84], supporting the relevance of protecting systems, including antioxidant defenses, to maintain neuronal integrity and survival [85].…”
Section: Mitochondria In Neurodegeneration: the Interplay Between Oximentioning
confidence: 96%
“…Moreover, ROS control the expression of highly conserved heat-shock proteins, and the increased mitochondrial ROS production can perturb the folding of proteins synthesized by mitochondria [79]. Finally, oxidation of cardiolipin's acyl chains at the mitochondrial inner membrane can cause respiratory complex destabilization [79,80]. Cardiolipin can interact with the respiratory chain complexes and contribute to generate the electrochemical gradient.…”
Section: Mitochondria In Neurodegeneration: the Interplay Between Oximentioning
confidence: 99%